The Development of Islamic Education Curriculum in Elementary Schools - Putri Nabila; Jesika Natalia; Selviani (The Future of Education Journal, 2025)
The aim of this study is to explore how elementary schools in Indonesia have developed and implemented their Islamic education curriculum. Based on the findings of the research, it was revealed that the current Islamic education curriculum in elementary schools has not reached its optimal potential. The existing curriculum still falls short in fostering a deep understanding of Islamic principles and encouraging students to apply them in their daily lives. This limitation in the curriculum design affects the overall development of students' religious knowledge and values. Additionally, the study found that many Islamic education instructors at the elementary school level do not possess the required qualifications or sufficient training to effectively teach the subject. This gap in qualifications and expertise among educators further exacerbates the challenges in delivering quality Islamic education. As a result, the study recommends a comprehensive overhaul of the Islamic education curriculum, making it more inclusive and better aligned with the current educational needs of students. The proposed curriculum should not only emphasize theoretical knowledge but also practical application, fostering a holistic understanding of Islam. Furthermore, it highlights the importance of providing specialized training and professional development opportunities for Islamic education teachers to enhance their teaching skills, knowledge, and pedagogical approaches. By improving both the curriculum and the qualifications of educators, it is expected that students will receive a more meaningful and effective Islamic education, which will better prepare them to live according to Islamic values and contribute positively to society.